2014
DOI: 10.1007/s00125-014-3163-6
|View full text |Cite
|
Sign up to set email alerts
|

Insulin pump use in pregnancy is associated with lower HbA1c without increasing the rate of severe hypoglycaemia or diabetic ketoacidosis in women with type 1 diabetes

Abstract: In this large multicentre study, women using insulin pumps in pregnancy had lower HbA1c without increased risk of severe hypoglycaemia or diabetic ketoacidosis but no improvement in other pregnancy outcomes. This information can help inform care providers and patients about the glycaemic effectiveness and safety of insulin pumps in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 32 publications
5
67
0
2
Order By: Relevance
“…The outcome of such a high-risk pregnancy is not easy to predict. A recent multicenter study in women using insulin pumps during pregnancy, just like in our small group, indicated a lower HbA1c without an increased risk of severe hypoglycemia 22 . All the patients wore insulin pump before becoming pregnant and started their pregnancy well prepared (were well educated and informed about lower targets).…”
Section: Discussionsupporting
confidence: 59%
“…The outcome of such a high-risk pregnancy is not easy to predict. A recent multicenter study in women using insulin pumps during pregnancy, just like in our small group, indicated a lower HbA1c without an increased risk of severe hypoglycemia 22 . All the patients wore insulin pump before becoming pregnant and started their pregnancy well prepared (were well educated and informed about lower targets).…”
Section: Discussionsupporting
confidence: 59%
“…This study was performed using data collected for a previous retrospective observational cohort analysis examining insulin pump use in pregnancy [17].…”
Section: Study Populationmentioning
confidence: 99%
“…All study centers used the same devices and the same methods of education and training for participants. However, a limitation was that, although studies comparing the use of CSII and MDI have yielded inconsistent results [23,29,[42][43][44][45][46], it was not possible to compare the results of pump use with a control group not using pump therapy and/or pump therapy supported by CGM. Nevertheless, this study offered a unique opportunity to follow a large patient population using standardized insulin-delivery devices to assess the prevalence of pregnancy complications and outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, insulin pump use in pregnancy has been found to reduce HbA 1c levels in patients with T1DM without increasing the rate of severe hypoglycemia or ketoacidosis [23]. Both CSII and continuous glucose monitoring (CGM), alone or in combination as a sensor-augmented pump (SAP) or sensor-integrated pump (SIP) therapy, improve glycemic control by reducing HbA 1c from 0.4-1.2% [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%